A Systematic Review and Narrative Synthesis of Risk Prediction Tools Used to Estimate Mortality, Morbidity, and Other Outcomes Following Major Lower Limb Amputation. (July 2021) - Preece, Ryan A.; Dilaver, Nafi; Waldron, Cherry-Ann; Pallmann, Philip; Thomas-Jones, Emma; Gwilym, Brenig L.; Norvell, Daniel C.; Czerniecki, Joseph M.; Twine, Christopher P.; Bosanquet, David C.
Abstract : Objective: The decision to undertake a major lower limb amputation can be complex. This review evaluates the performance of risk prediction tools in estimating mortality, morbidity, and other outcomes following amputation. Methods: A systematic review was performed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The MEDLINE, Embase, and Cochrane databases were searched to identify studies reporting on risk prediction tools that predict outcomes following amputation. Outcome measures included the accuracy of the risk tool in predicting a range of post-operative complications, including mortality (both short and long term), peri-operative morbidity, need for re-amputation, and ambulation success. A narrative synthesis was performed in accordance with the Guidance on the Conduct of Narrative Synthesis In Systematic Reviews. Results: The search identified 518 database records. Twelve observational studies, evaluating 13 risk prediction tools in a total cohort of 61 099 amputations, were included. One study performed external validation of an existing risk prediction tool, while all other studies developed novel tools or modified pre-existing generic calculators. Two studies conducted external validation of the novel/modified tools. Nine tools provided risk estimations for mortality, two tools provided predictions for post-operative morbidity, two for likelihood of ambulation, and one for re-amputation to the same or higher level. Most mortality prediction tools demonstrated acceptable discrimination performance with C statistic values ranging from 0.65 to 0.81. Tools estimating the risk of post-operative complications (0.65 – 0.74) and necessity for re-amputation (0.72) also performed acceptably. The Blatchford Allman Russell tool demonstrated outstanding discrimination for predicting functional mobility outcomes post-amputation (0.94). Overall, most studies were at high risk of bias with poor external validity. Conclusion: This review identified several risk prediction tools that demonstrate acceptable to outstanding discrimination for objectively predicting an array of important post-operative outcomes. However, the methodological quality of some studies was poor, external validation studies are generally lacking, and there are no tools predicting other important outcomes, especially quality of life.